2019
DOI: 10.30569/adiyamansaglik.486946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antioxidant mRNA expression levels of advanced Protruded and Extruded Nucleus Pulposus in Degenerative Lumbar Disc Herniations using the RT-PCR method

Abstract: The aim of the present study is to compare the antioxidant levels of nucleus pulposus in advanced protruded and extruded lumbar disc hernias (LDH) with a steady lumbar posterior longitudinal ligament with the Real Time-Polymerase Chain Reaction (RT-PCR) method. Method: This study was conducted with the comparison of the disc sections of a total of 40 patients who underwent an operation due to advanced protruded (n=20) and extruded (n=20) LDH with the TRI-Reagent ® and Ribonucleic acid (RNA) isolation and the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies have evaluated the levels of antioxidant mRNA in cases of Intervertebral Disc Herniation (IDH) (5). It has also been reported that oxidative stress increases apoptosis in various components of the disc and accelerates the formation of intervertebral disc degeneration by inducing apoptosis in the endplate chondrocytes, nucleus pulposus cells and annulus fibrosus cells of the disc (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have evaluated the levels of antioxidant mRNA in cases of Intervertebral Disc Herniation (IDH) (5). It has also been reported that oxidative stress increases apoptosis in various components of the disc and accelerates the formation of intervertebral disc degeneration by inducing apoptosis in the endplate chondrocytes, nucleus pulposus cells and annulus fibrosus cells of the disc (6).…”
Section: Introductionmentioning
confidence: 99%